El proselitismo político y su impacto en la democracia ecuatoriana - Cantos Suquillo, Mayra (2025)
Political proselytism in Ecuador has significantly impacted the country's democracy. Through various communication and mobilization strategies, political parties aim to influence public opinion and gain electoral support. However, this phenomenon can also lead to polarization and distrust in democratic institutions. It is essential to analyze how proselytism affects citizen participation and the quality of political debate, as well as its role in building a stronger and more representative democracy. Recent examples, such as the removal of councilors by the Electoral Court, highlight the need to strengthen regulations to protect neutrality in public offices and ensure democratic stability.